2009
DOI: 10.1088/0004-637x/691/2/l138
|View full text |Cite
|
Sign up to set email alerts
|

The Mass-Metallicity Gradient Relation of Early-Type Galaxies

Abstract: We present a newly observed relation between galaxy mass and radial metallicity gradients of earlytype galaxies. Our sample of 51 early-type galaxies encompasses a comprehensive mass range from dwarf to brightest cluster galaxies. The metallicity gradients are measured out to one effective radius by comparing nearly all of the Lick absorption-line indices to recent models of single stellar populations. The relation shows very different behavior at low and high masses, with a sharp transition being seen at a ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
171
2
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(209 citation statements)
references
References 40 publications
35
171
2
1
Order By: Relevance
“…Looking further into its integrated spectrum (global and nuclear, see Fig. 3), we noticed that (i) the emission lines are broad, which is a possible sign of nuclear activity; (ii) the two nitrogen lines are clearly visible, as is the sulfur doublet and the [O i]6300 line, which together are characteristics of LINER galaxies, often associated to AGNs (Heckman 1980) -or violent episodes of star-formation in highmetallicity galaxies (Terlevich & Melnick 1985).…”
Section: Agn Contaminationmentioning
confidence: 90%
See 1 more Smart Citation
“…Looking further into its integrated spectrum (global and nuclear, see Fig. 3), we noticed that (i) the emission lines are broad, which is a possible sign of nuclear activity; (ii) the two nitrogen lines are clearly visible, as is the sulfur doublet and the [O i]6300 line, which together are characteristics of LINER galaxies, often associated to AGNs (Heckman 1980) -or violent episodes of star-formation in highmetallicity galaxies (Terlevich & Melnick 1985).…”
Section: Agn Contaminationmentioning
confidence: 90%
“…They appear to correlate with macroscopic properties such as stellar mass (e.g. Spolaor et al 2009). It has been demonstrated that a metallicity gradient in the stellar populations could survive a major merger event, although it will be weakened.…”
Section: Introductionmentioning
confidence: 99%
“…In the canonical scenario, a galaxy's initial metallicity gradient is set by an initial starburst at z 3 and the metallicity decreases in the outskirts, as metallicity follows the changes in the gravitational potential (Scott et al 2009;McDermid et al 2012). This gradient can be disrupted by violent merging events (major mergers), or reinforced by minor mergers (Kobayashi 2004;Spolaor et al 2009;Cooper et al 2010;Pipino et al 2010). Hirschmann et al (2014) analysed the stellar populations of 10 massive halos (10 12 < M halo < 10 13 M ) from the high-resolution cosmological simulation of Hirschmann et al (2013).…”
Section: Introductionmentioning
confidence: 99%
“…These SBF gradients represent a powerful and independent tool to understand how stellar populations have evolved within galaxies. As discusses by Cantiello et al (2005), the radial change of SBF magnitudes, or SBF colours, in a galaxy can be a valuable tool to constrain formation mechanism theories: steep gradientscorrelated with the galactic mass -support dissipative collapse scenarios (Carlberg 1984;Davies et al 1993;Spolaor et al 2009), while shallow gradients are expected in the hierarchical merging picture (Kauffmann et al 1993;Bekki & Shioya 2001;La Barbera et al 2004). Therefore, the radial behaviour of stellar population properties contains a footprint of the galaxy star-formation history but, while modern versions of the monolithic or hierarchical formation scenarios have shown that they are able to reproduce in part the observed behaviour of earlytype galaxies, none of the proposed scenarios has proved to be decisively successful over the other (Kampakoglou et al 2008;Foster et al 2009).…”
Section: Introductionmentioning
confidence: 99%